Highly accurate, reliable, and non-contaminating two-dimensional material transfer system - Patil, Chandraman; Dalir, Hamed; Kang, Jin Ho; Davydov, Albert; Wong, Chee Wei; Sorger, Volker J. (Applied physics reviews, 2022)
The exotic properties of two-dimensional materials and heterostructures, built by forming heterogeneous multi-layered stacks, have been widely explored across several subject matters following the goal to invent, design, and improve applications enabled by these materials. Successfully harvesting these unique properties effectively and increasing the yield of manufacturing two-dimensional material-based devices for achieving reliable and repeatable results is the current challenge. The scientific community has introduced various experimental transfer systems explained in detail for exfoliation of these materials; however, the field lacks statistical analysis and the capability of producing a transfer technique enabling (i) high transfer precision and yield, (ii) cross-contamination free transfer, (iii) multi-substrate transfer, and (iv) rapid prototyping without wet chemistry. Here, we introduce a novel two-dimensional material deterministic transfer system and experimentally show its high accuracy, reliability, repeatability, and non-contaminating transfer features by demonstrating fabrication of two-dimensional material-based optoelectronic devices featuring novel device physics and unique functionality. The system paves the way toward accelerated two-dimensional material-based device manufacturing and characterization. Such rapid and material analyzing prototype capability can accelerate not only layered materials science in discovery but also engineering innovations.